Influence of Organizational Citizenship Behaviour on Mauritian Hospitality Industry employee job- satisfaction: Structural Equation Modelling. - Ramesh, Vani (International Journal of Psychosocial Rehabilitation, 2020)
Purpose and Background: Mauritius is a center of attraction and considered a paradise on the planet with an astonishing perspective and resources to attract and accommodate the customers of the `Hospitality Industry`. This study, being first and foremost in the country, aims at examining the influence of ` Organizational Citizenship Behaviour` (OCB) on Job Satisfaction of employees associated with the Mauritian Hospitality Industry. Later and Organ`s 5 dimensions of OCB, such as `Altruism`; `Courtesy`; `Civic Virtue`; `Conscientiousness`; and,`Sportsmanship` is tested for the Island context to understand employee job-satisfaction. Job-satisfaction is cognitive and affective evaluation of the job engaged and OCB as a mediating mechanism that influences the `Job- satisfaction` and `Organizational Commitment` to `Citizenship Behaviour`.Research Design: The data is gathered administering well-structured questionnaire with 5-point Likert scale, and a drop-off survey is adopted. The response rate is reasonably suitable for the analysis (Cronbach`s Alpha, 0.893/ KMO, and Bartlett`s, .868) with the sample size of 332 respondents. All tourists’ centers, including resorts, hotels, beaches, travels, amusement parks, and shopping malls, are surveyed to collect the data from the employees. PASW Statistics 18, MS Excel 2007 and Smart PLS and IBM SPSS AMOS used. Exploratory and Confirmatory Factor Analysis (ECFA) is computed first with the help of AMOS to identify the factors suitable to validate the hypothesis. Later SEM is calculated for the model specification followed by a path diagram. Also, necessary care has been taken for the outliers’ detection to avoid hurdles for the analysis.Results and Findings: The structural model estimates that all the direct influences are the significant impact of OCB on job-satisfaction, and OCB is playing a mediating role on Jo satisfaction. Also found employees with organizational commitment and citizenship behavior are more satisfied with their job.Conclusion, Implications, and further research: OCB should form a part of the Mauritian Hospitality Industry to motivate the employees. Motivated and satisfied employees are more effective and efficient in their work. Though there are many studies conducted on similar grounds in other countries, for Mauritius, this is the first study contributing extensively to the literature. Also, it provides an excellent platform for academics, researchers, Hospitality Industry, and stakeholders, policymakers to understand the mediating role of OCB in improving `job- satisfaction` and `performance` of the employees of the hospitality industry. For further research, there can be a broader scope for testing the variables in-depth with more number of observations.